Life cycle cost analysis of MEG regeneration process incorporating a modified slip stream concept. (20th July 2017) - Kim, Hyunho; Lim, Youngsub; Seo, Yutaek; Ko, Minsu
Highlights: This study proposed a modified concept for the MEG regeneration process. The precipitation of NaCl was prevented by implementing a two-stage distillation. The modified concept showed few precipitation under a high TDS of up to 224 g/L. Economic benefit was 9.8% decrease in CAPEX and 8.6% decrease in OPEX. Abstract: This study proposes a modified concept for mono ethylene glycol (MEG) regeneration process to prevent the precipitation of monovalent salt (NaCl) and to economize on efficient energy use with operational flexibility. Two-stage distillation was that the second distillation column was operated after the removal of the monovalent salt while controlling the performance of the first distillation column. This modified concept was evaluated according to (i) the possibility of salt precipitation in the re-boiler of the column at various salinity in the produced water (35–224 g/L) and (ii) the economic feasibility compared to a conventional concept where water is evaporated off using a single stage distillation column. The salt precipitation was investigated using the ENRTL-RK property in ASPEN PLUS. The conventional concept showed a high risk of NaCl precipitation in the column when the feed stream contains a high salinity. The modified concept showed few precipitation in the column with a high salinity in feed stream. Then, ASPEN PLUS economic analyzer were used to construct the economic evaluation according to the Life Cycle Cost (LCC) methodology including CAPEX and OPEX. The modified concept showed 9.8% decrease in CPAEX and 8.6% decrease in OPEX compared to the conventional concept. The sensitivity analysis showed that the inlet flow rate and the concentration of rich MEG were the most significant factors that affected the economic viability of the MEG regeneration process, and the modified concept was less sensitive to the inlet condition change than the conventional concept.